Forests are chill: The interplay between thermal comfort and mental wellbeing - GILLEROT, Loïc (Institutional Knowledge at Singapore Management University, 2024)
As global warming and urbanisation intensify unabated, a growing share of the human population is exposed to dangerous heat levels. Trees and forests can effectively mitigate such heat alongside numerous health co-benefits like improved mental wellbeing. Yet, which forest types are objectively and subjectively coolest to humans, and how thermal and mental wellbeing interact, remain understudied. We surveyed 223 participants in peri-urban forests with varying biodiversity levels in Austria, Belgium and Germany. Using microclimate sensors, questionnaires and saliva cortisol measures, we monitored intra-individual changes in thermal and mental states from non-forest baseline to forest conditions. Forests reduced daytime modified Physiologically Equivalent Temperature (mPET; an indicator for perceived temperature) by an average of 9.2 ◦C. High diversity forests were the coolest, likely due to their higher stand density. Forests also lowered thermal sensation votes, with only 1 % of participants feeling ‘warm’ or ‘hot’ compared to 34 % under baseline conditions. Despite the desire for a temperature increase among 47 % participants under cool forest conditions, approximately two-thirds still reported feeling very comfortable, in contrast to only one-third under baseline conditions. Even at a constant perceived temperature, participants were 2.7 times more likely to feel warmer under baseline conditions compared to forests. A forest-induced psychological effect may underlie these discrepancies, as supported by significant improvements in positive and negative affect (emotional state), state anxiety and perceived stress observed in forests. Additionally, thermal and mental wellbeing were significantly correlated, indicating that forest environments might foster a synergy in wellbeing benefits.